The role of modifiable risk factors on the cerebral myelin content and cognition: findings from The Maastricht Study - Gerhard S. Drenthen; Walter H. Backes; Sebastian Köhler; Kay Deckers; Miranda T. Schram; Simone J. P. M. Eussen; Willemijn J. Jansen; Jacobus F. A. Jansen (GeroScience, 2026)
Lifestyle-related factors may affect cognition and increase the risk of developing dementia. However, the neurobiological mechanisms underlying the effect of lifestyle-related factors on the brain are not yet fully understood. Myelin, a vital element of brain health, has previously been shown to be involved in dementia-related cognitive decline. However, whether it plays a role in the relation between lifestyle-related factors and cognitive performance has not been studied. The cerebral myelin content of 4653 participants (51% female, aged 59 ± 9 years) from The Maastricht Study was estimated using the T1w/FLAIR-ratio, and lifestyle-related factors were summarized using the LIBRA-score. Multivariable linear regression models, corrected for the effects of age, sex and education, were used to investigate whether lifestyle-related factors are associated with myelin. Moreover, whether myelin can partly explain the relationship between lifestyle-related factors and cognition was explored using a mediation analysis across three cognitive domains (memory, executive functioning and processing speed). An unhealthy lifestyle (i.e. higher LIBRA score) is significantly associated to a lower cerebral myelin content ( β = −0.24, 95% CI [−0.26 −0.22], and p < 0.001). Furthermore, lower cerebral myelin content associates to worse cognitive performance ( β = 0.14, 95% CI [0.11 0.17], and p < 0.001). Moreover, myelin has a partially mediating effect of 15%, indicating that it partly explains the relation between lifestyle-related factors and cognition. These results show that myelin content might help explain the mechanisms through which lifestyle-related factors influence cognition, potentially allowing for specific and early lifestyle interventions aimed at preventing or delaying cognitive decline and dementia. Graphical abstract